Advances in Engine and Powertrain Research and Technology c - Parikyan, Tigran; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The book covers a wide range of applied research compactly presented in one volume, and shows innovative engineering solutions for automotive, marine and aviation industries, as well as power generation. While targeting primarily the audience of professional scientists and engineers, the book can also be useful for graduate students, and also for all those who are relatively new to the area and are looking for a single source with a good overview of the state-of-the-art as well as an up-to-date information on theories, numerical methods, and their application in design, simulation, testing, and manufacturing. The readers will find here a rich mixture of approaches, software tools and case studies used to investigate and optimize diverse powertrains, their functional units and separate machine parts based on different physical phenomena, their mathematical representation, solution algorithms, and experimental validation.
Dynamics and Vibrations / Tribology and Lubrication -- Combustion / CFD / Emissions / Fuels -- Hybrid and Electrified Powertrains -- Testing / Calibration / Monitoring / Diagnostics -- Manufacturing. .
Keywords: Automotive engineering; Multibody systems; Vibration; Mechanics, Applied; Industrial engineering; Production engineering; Automotive Engineering; Multibody Systems and Mechanical Vibrations; Industrial and Production Engineering; Automobiles -- Power trains -- Design and construction; Engines -- Design and construction